The Origins of Foreign Exchange Policy: The National Bank of Belgium and the Quest for Monetary Independence in the 1850s - Stefano Ugolini (Norges Bank, 2010)
Can the central bank of a small open economy be mandated with the maintenance of both fixed exchange rates and monetary independence, and still succeed in the long term? Looking at a pioneering experiment put in place by the National Bank of Belgium, this article shows how foreign exchange policy allowed for persistent violations of the predictions of the trilemma in the 1850s. Success was based on four main ingredients. First, the credibility of the peg was not built through the stabilisation of exchange rates, but through the stabilisation of central bank liquidity (i.e. the 'margin of manoeuvre' available for countercyclical action): based on constructive ambiguity, this strategy positively influenced market expectations. Second, the stock of bullion circulating in the country acted as a buffer for central bank reserves. Third, the banking system had a structural liquidity deficit towards the central bank. Fourth, the central bank was big enough to meet the domestic demand of credit and accumulate foreign reserves at the same time. These findings shed new light on the nature of monetary policy and its implementation in the 19th century.
hdl:11250/2497439
Keywords: E52; E58; F31; N23; 330; foreign exchange policy; monetary policy implementation; reserve management